Monodispersed Li4Ti5O12 with Controlled Morphology as High Power Lithium Ion Battery Anodes. Issue 7 (31st May 2016) - Li, Yunchao; Fu, Guoyi; Watson, Mark; Harrison, Stephen; Paranthaman, M. Parans
Abstract: Monodispersed Li4 Ti5 O12 (LTO) nanoparticles with controlled microstructure were successfully synthesized by a combination of hydrolysis and hydrothermal method followed by a post‐annealing process. The scanning electron microscopy images showed that particles with a size of 30–50 nm were precisely controlled throughout the synthesis process. The electrochemical tests of the as‐prepared LTO electrodes in a half‐cell proved its high rate performance and outstanding cyclability which benefits from the preserved well‐controlled nanoparticle size and morphology. LTO electrodes were also tested in a full cell configuration in pairing with LiFePO4 cathodes, which demonstrated a capacity of 147.3 mA h g −1 . In addition, we have also demonstrated that LTO materials prepared using lithium salts separated from geothermal brine solutions had good cyclability. These demonstrations provide a promising way for making low‐cost, large‐scale LTO electrode materials for energy storage applications. Abstract : Monodispersed Li4 Ti5 O12 (LTO) nanoparticles were prepared with precise control of the particle size between 30–50 nm throughout the synthesis process. The as‐prepared LTO electrodes demonstrated high rate performance and outstanding cyclability, which benefits from the preserved well‐controlled nanoparticle size and morphology.